Magnetically regulated collapse in the B335 protostar? I. ALMA observations of the polarized dust emission. Issue 2 (3rd March 2018) - Maury, A J; Girart, J M; Zhang, Q; Hennebelle, P; Keto, E; Rao, R; Lai, S-P; Ohashi, N; Galametz, M
Abstract: The role of the magnetic field during protostellar collapse is poorly constrained from an observational point of view, although it could be significant if we believe state-of-the-art models of protostellar formation. We present polarimetric observations of the 233 GHz thermal dust continuum emission obtained with ALMA in the B335 Class 0 protostar. Linearly polarized dust emission arising from the circumstellar material in the envelope of B335 is detected at all scales probed by our observations (50 to 1000 au). The magnetic field structure producing the dust polarization has a very ordered topology in the inner envelope, with a transition from a large-scale poloidal magnetic field, in the outflow direction, to strongly pinched in the equatorial direction. This is probably due to magnetic field lines being dragged along the dominating infall direction since B335 does not exhibit prominent rotation. Our data and their qualitative comparison to a family of magnetized protostellar collapse models show that, during the magnetized collapse in B335, the magnetic field is maintaining a high level of organization from scales 1000 au to 50 au: this suggests the field is dynamically relevant and capable of influencing the typical outcome of protostellar collapse, such as regulating the disc size in B335.